Determinants of Investments Decisions in Economics and Business Faculty Students at Pelita Bangsa University - Ibnu Andaris; Sunita Dasman (Universitas Negeri Padang, 2024)
The present study endeavors to undertake an in-depth analysis of the impact of financial literacy, overconfidence, and risk tolerance on investment decisions in a structured manner by employing the conceptual framework of prospect theory. The research methodology is based on quantitative research utilizing primary data obtained through the distribution of questionnaires to all the students of the business economics faculty at Pelita Bangsa University. A sample of 101 respondents was used in the research, and the data was processed using the smart-pls 3 software program with a partial least squares approach. The research findings indicate that financial literacy has a significant positive influence on investment decisions, whereas overconfidence has a positive but insignificant influence on investment decisions. Furthermore, risk tolerance has a positive and significant effect on making investment decisions. The most prominent implication of the study is found in the financial literacy section, which suggests that a deeper understanding of financial literacy can lead to more accurate investment decisions. Additionally, an investor's overconfidence and risk tolerance also play a role in making investment decisions.